Caracterização, sazonalidade e atividade inseticida de acessos de Varronia curassavica Jacq. - Oliveira, Bruna Maria Santos de (2019)
Erva-baleeira (Varronia curassavica Jacq.), belonging to the Cordiaceae family, is a medicinal and aromatic plant native to Brazil. Its essential oil is used by the pharmaceutical industry, as it contains bioactive substances. The production and yield of essential oils by medicinal and aromatic plants may be influenced by biotic and abiotic factors. An alternative for maintaining and preserving plant diversity is the formation of Active Germplasm Banks (AGBs). Therefore, the goal of this study was to chemically and morpho-agronomically characterize accessions of V. curassavica from the Active Germplasm Banks of medicinal and aromatic plants of the Federal University of Sergipe (UFS) harvested during the rainy season (July 2015) and dry season (January 2016). An additional goal was to evaluate the lethal and sub-lethal effects of the essential oils and their constituents, E-caryophyllene and α-humulene, on the ant Dorymyrmex thoracicus. Morphological analysis was carried out in the field by evaluating plant height; canopy width; canopy shape; stem diameter; stem color; leaf blade width, length, and length/width ratio; and leaf, petal, and sepal colors. Agronomic analysis was performed by analyzing leaf dry matter and content and yield of the essential oil. The essential oils extracted from the dried leaves were chemically analyzed by hydrodistillation in an adapted Clevenger device, with identification by chemical analysis through Gas Chromatography / Mass Spectrometry / Flame Ionization Detection (GC/MS/FID). The lethal and sub-lethal effects of the essential oils and their constituents E-caryophyllene and α-humulene were evaluated through bioassays of fumigation toxicity and locomotor activity in partially treated arenas. In morphological and agronomic evaluation, the existence of phenotypic variability in the V. curassavica collection was observed. In chemical analysis, seven chemical groups were formed within the two harvest periods. The clusters were characterized by the presence of the following chemical compounds: cluster 1 – methyl-9-methylene-2-isopropylcyclodec-4-en-1-one; cluster 2 – E-caryophyllene and α-turmerone; cluster 3 – methyl-9-methylene-2-isopropylcyclodec-4-en-1-one, α-turmerone, and E-caryophyllene; cluster 4 – shyobunol and germacrene D-4-ol; cluster 5 – E-caryophyllene, viridiflorol, and α-zingiberene; cluster 6 – sabinene, E-caryophyllene, and bicyclogermacrene; and cluster 7 – α-pinene and E-caryophyllene. Small quantitative variations of the chemical constituents of the essential oil of the accessions were observed within the two seasons. Only the accessions VCUR-302 and VCUR-502 had major changes in the chemical composition of their essential oils. These two accessions migrated from cluster 5 in the rainy season to cluster 6 in the dry season. The accession VCUR-105 had higher essential oil content in the rainy season (3.20%). In the dry season, the accessions VCUR-003 (2.78%) and VCUR-101 (2.73%) were also productive, as well as VCUR-105 (2.84%). The bioactive compounds α-humulene and E-caryophyllene were detected in all accessions in both seasons. The lethal concentrations to kill 50% of the D. thoracicus population ranged from 0.69 to 2.48 μL L-1 for essential oils and from 3.754 to 1.493 μL L-1 for the E-caryophyllene and α-humulene compounds. In general, the essential oils of V. curassavica caused repellency and affected the locomotor activity of the ants. These results indicate that essential oils of V. curassavica are a promising source for control of the urban ant D. thoracicus.